2004
DOI: 10.1108/02621710410546678
|View full text |Cite
|
Sign up to set email alerts
|

Optimising skills transfer via outdoor management development

Abstract: Despite rapid expansion in provision of outdoor management development (OMD), there is a lack of empirical evidence to support the efficacy of the learning process and crucially, its transfer to the workplace. Prompted by the dearth of research into the linkage between programme aims, the methodologies utilised and outcomes that are purported to accrue, a new framework for analysing the mechanisms of skills transfer is proposed. The framework represents a decision making chain comprised of three factors i.e. t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…Notably, the results of this study also strongly suggested that the program caused a reduction in employee sick days and improvements in quality improvement results-that is, positive outcomes at the organizational level (Kirkpatrick, 1996). An investigation of participants' perceptions of efficacy of different OMD approaches for transfer of learning to the workplace (Burke & Collins, 2004) also suggests some degree of retention and/or use of learning.…”
Section: Professional Development and Adventure Educationmentioning
confidence: 99%
“…Notably, the results of this study also strongly suggested that the program caused a reduction in employee sick days and improvements in quality improvement results-that is, positive outcomes at the organizational level (Kirkpatrick, 1996). An investigation of participants' perceptions of efficacy of different OMD approaches for transfer of learning to the workplace (Burke & Collins, 2004) also suggests some degree of retention and/or use of learning.…”
Section: Professional Development and Adventure Educationmentioning
confidence: 99%
“…Representative design is considered the most effective way of maximizing the potential for contextualized individual learning relevant for the everyday performance environment of the learner. Recognition of the need to design programmes that reflect everyday environments is already apparent in outdoor management development [78,79], yet not readily utilised in AEP. From an ED perspective, for learning to be useful in an everyday context, representative design is key.…”
Section: Representative Designmentioning
confidence: 99%
“…Outdoor, adventure and experiential education (OAE) is widely used and acknowledged as effective pathway to promote personal and social skills and competencies that are relevant in professional life contexts (Burke & Collins, 2004a). Many outdoor education providers offer specific programmes for apprentices, work groups, and managers, with costumer companies returning year after year with high satisfaction, rendering this "a multi-million pound international industry" (Jones & Oswick, 2007, 327).…”
Section: Introductionmentioning
confidence: 99%